Intensification of heatwaves in China in recent decades: Roles of climate modes - Jia Wei; Weiqing Han; Weiguang Wang; Lei Zhang; Balaji Rajagopalan (npj Climate and Atmospheric Science, 2023)
Abstract Modes of climate variability can affect weather extremes, posing intractable challenges to our environment. However, to what extent climate modes can modulate heatwaves in China under a warming background remains poorly understood. Here, we examine the changes in heatwave intensity in seven distinct regions: three East, two middle, and two west regions over China and systematically explore the impacts of climate modes, by analyzing observations and performing model experiments using a Bayesian dynamic linear model and an atmospheric general circulation model (AGCM). Abrupt increases in heatwave intensity are detected across China during a transition period of 1993–2000, and the intensification remains robust in northern and western China after the warming trend being removed. The combined impacts of the El Niño–Southern Oscillation (ENSO), Atlantic Multidecadal Oscillation (AMO), and Indian Ocean Dipole (IOD) explain 62.35–70.01% of the observed heatwave intensification in East I, Middle I, West I, and West II regions. Decadal changes of atmospheric circulations associated with the negative phase transition of the Interdecadal Pacific Oscillation (IPO), which is highly correlated with the decadal variability of ENSO, combined with the positive phase transition of the AMO around the mid-1990s increase surface air temperature and enhance atmospheric internal variability and climate modes’ impacts, resulting in the abrupt increase of heatwaves in the past two decades. These results highlight the importance of the concurrent phase transitions of decadal climate modes in regulating heatwaves.